Sizing of single fluorescently stained DNA fragments by scanning microscopy - Laib, Stephan (Oxford University Press, 2003)
We describe an approach to determine DNA fragment sizes based on the fluorescence detection of single adsorbed fragments on specifically coated glass cover slips. The brightness of single fragments stained with the DNA bisintercalation dye TOTO-1 is determined by scanning the surface with a confocal microscope. The brightness of adsorbed fragments is found to be proportional to the fragment length. The method needs only minute amount of DNA, beyond inexpensive and easily available surface coatings, like poly-l-lysine, 3-aminoproyltriethoxysilane and polyornithine, are utilizable. We performed DNA-sizing of fragment lengths between 2 and 14 kb. Further, we resolved the size distribution before and after an enzymatic restriction digest. At this a separation of buffers or enzymes was unnecessary. DNA sizes were determined within an uncertainty of 7–14%. The proposed method is straightforward and can be applied to standardized microtiter plates.